MARKET ORIENTASION EFFECT ON THE PERFORMANCE OF THE PRODUCT PROCESSED FISH MARKETING SMEs IN JAMBI - AGESHA MARSYAF; ADE OCTAVIA; ERIDA ERIDA (Journal of Business Studies and Management Review, 2019)
The address of this research is to analyze the effect of market orientation toward. the performance of Micro, Small and Medium entreprises in the field of Fish processing Products in Jambi City, either simultaniously or partially. The sample of this research are represented by 45 MSME’s. This study utilized linear regression analysis. Data of this research was tabulated from respondent responsiveness. The results of this study prove that simultaneously the performance of Micro, Small and Medium entreprises is significant influenced by the market orientation. Furthermore, partially the results show that the customer orientation and competitor orientation have a significant effect toward the performance of MSME. On the other hand, the coordination of inter-function has not significant effect partially toward the performance of MSME. The study suggests for the entrepreneur of Micro, Small and Medium entreprises to improve the function of their internal coordination and give a wider delegation to their employers to do their tas